Solid and liquid modernity: A comparison of the social geography of places to die in the UK and Australia. Issue 2 (7th February 2017) - Randall, Duncan; Rosenberg, John P.; Reimer, Suzanne
ABSTRACT: Preferred place of care and death is a widely used quality measure for palliative and end of life care services. In this article we explore the use of Zygmunt Bauman's ideas on solid and liquid modernity to understand the complexity of the social geographical contexts of delivering and receiving care. Although solid ways of dying offer certainty and standardized care, more liquid ways allow for individualized care connected to family and communities. Understanding the complex tensions between solid and liquid aspects of palliative care may allow practitioners to help dying people to die in the ways and places they prefer.